Employee Competency Development Strategy in the Digital Transformation Era: Approach from an HR Development Perspective - Desi Kristanti; Hariyanti, Sri (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Digital transformations are profoundly altering business paradigms, necessitating organizations to revise their HR strategies. Competency development among employees emerges as a pivotal factor in organizational success amidst rapid technological shifts. Employing a qualitative approach, this study aims to pinpoint effective strategies for employee competency development in the digital transformation era. Utilizing interviews, observations, and document analysis, the research aims to uncover best practices including continuous training, career development, mentoring, and the integration of digital transformation with employee growth. The implications for HR management are substantial, demanding adjustments in designing competency programs aligned with technological advancements. This study offers valuable insights for HR and management practitioners navigating challenges in the digital transformation era.